2017
DOI: 10.2196/mental.6805
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Equivalence of Paper, Mobile Phone, and Tablet Survey Responses at a Community Mental Health Center Using Equivalent Halves of a ‘Gold-Standard’ Depression Item Bank

Abstract: BackgroundThe computerized administration of self-report psychiatric diagnostic and outcomes assessments has risen in popularity. If results are similar enough across different administration modalities, then new administration technologies can be used interchangeably and the choice of technology can be based on other factors, such as convenience in the study design. An assessment based on item response theory (IRT), such as the Patient-Reported Outcomes Measurement Information System (PROMIS) depression item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, although one recent study did find that the method of survey administration has a clinically significant effect on the measurement of PROMIS UE scores, 42 numerous studies of a variety of PROMIS instruments found no such difference. 5 , 7 , 22 Another limitation of the present study is the mean follow-up period of 472 days. A study with a shorter or longer mean follow-up period may yield different results, due to both the longitudinal changes in subjects’ physical function after surgery as well as the increase in recall bias inherent to longer follow-up periods in anchor-based MCID calculations.…”
Section: Discussionmentioning
confidence: 92%
“…However, although one recent study did find that the method of survey administration has a clinically significant effect on the measurement of PROMIS UE scores, 42 numerous studies of a variety of PROMIS instruments found no such difference. 5 , 7 , 22 Another limitation of the present study is the mean follow-up period of 472 days. A study with a shorter or longer mean follow-up period may yield different results, due to both the longitudinal changes in subjects’ physical function after surgery as well as the increase in recall bias inherent to longer follow-up periods in anchor-based MCID calculations.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the washout period was 2 hours. In addition, some researchers have tried new methods to overcome these challenges, such as creating two functionally equivalent halves of the item bank [ 33 ]. However, for the ASES questionnaire, there are relatively few items, and each item evaluates a specific functional direction, so this method cannot be adopted.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one study found that text message responses from participants were more candid than responses from voice interviews [ 18 ]. Text message surveys yield data that are comparable with other paper and online assessment tools [ 19 , 20 ], while overcoming many of the limitations of these traditional approaches (ie, interviews, computer-assisted surveys, and school-based assessments) [ 4 , 7 , 21 , 22 ]. For example, real-time text message data can reduce recall biases inherent in costly assessments that may be several months or years apart [ 5 , 23 ].…”
Section: Introductionmentioning
confidence: 99%